History's Muse : the prose writings of Thomas Moore - Kelly, Ronan (Trinity College (Dublin, Ireland). School of English, 2002)
Since his heyday in the nineteenth century Thomas Moore (1779 - 1852) has often been considered Ireland’s national poet, principally because of his Irish Melodies (ten numbers, 1808 - 34). However, from the mid-1820s on, he turned increasingly to prose, almost all of which enjoyed both critical and commercial acclaim. In contrast to the Melodies, this prose was often divisive and occasionally sectarian, and for this reason was largely excluded from the reputation of Moore that was popularised after his death. This exclusion proved enduring: the most recent book-length biography of Moore is dismissive of the prose works, while Seamus Deane’s introduction to the writer in the Field Day Anthology contains a single, fleeting, and misleading reference to their existence. As a corrective to this view, this thesis argues that the prose was in fact a vital part of Moore’s oeuvre. Furthermore, it demonstrates that the prose significantly deepens our appreciation of not only the range of Moore’s literary achievement, but also the nature of his complex political allegiances.
Keywords: English, Ph.D.; Ph.D. Trinity College Dublin